Homo patiens: implicações filosófico-teológicas da experiência do sofrimento - Oliveira, Cláudia Maria Rocha de (Horizonte, 2020)
This article intends to present the experience of suffering as an enigma to reason and a challenge to faith, following Paul Ricoeur’s philosophy. Ethic and religious expressions of evil, understood as transgression and sin, are related to an active attitude, to an act of making. Innocent suffering, on the contrary, should be considered from the perspective of the victim. How to justify the pain of innocent victims of catastrophes, incurable diseases, violence? Is it possible, for example, to confer sense of the experience of the suffering of families that lose the fight against COVID-19? If God is fair, how could he allow the suffering of innocent people? The first part of the text will present how Paul Ricoeur understands the problem of evil from three main dimensions: the ethic dimension of transgression, the religious dimension of sin, and the dimension of innocent suffering. The second part will discuss the way Ricoeur regards suffering as challenge. According to Ricoeur, traditional dialectics is not able to provide meaning to innocent suffering. The problem of evil demands a convergence between thought and action, as well as the spiritual transformation of feelings. That transformation, which should lead to a disinterested love of God, assumes a specific understanding of the relation between love and justice.